PENGEMBANGAN E-LKPD FISIKA BERBASIS PROBLEM BASED LEARNING BERMUATAN PENDIDIKAN KARAKTER UNTUK PESERTA DIDIK KELAS XI DI SMA N 12 PADANG : jurnal - Amelinda, Viona Alda; trisna, silvi; rahmi, aidhia (Jurnal Pendidikan Fisika Undiksha, 2023)
In the learning process students can be said not to be active. The learning process still uses printed teaching materials such as textbooks and LKS. The learning model is in the form of lectures and questions and answers. Along with technological developments, the learning process must be able to utilize technology, such as the formation of teaching materials. One of the teaching materials developed is in the form of E-LKPD. The purpose of this study was to develop a valid and practical E-LKPD Physics Based on Problem Based Learning with Character Education for Class XI Students at SMA N 12 Padang. This type of research is development (Research and Development) using the 4D development model. The instruments used were validity and practicality sheets, used to determine the validity and practicality of the teaching materials developed. The percentage level of validity is based on material experts and media experts, the validation average is 89.77% which is categorized as very valid. The practicality percentage of the media is 92% which is categorized as very practical. So that the teaching materials developed are categorized as very valid and very practical to use in the learning process.